Phase II study of a three-dose primary vaccination course of DTPa-IPV/Hib-MenC-TT followed by a 12-month Hib-MenC-TT booster in healthy infants. (24th May 2012) - Khatami, A; Snape, MD; Ohene-Kena, B; Young, K; Oeser, C; Heath, PT; Michaelis, L; McLeod, E; Faust, S; Smee, H; Finn, A; Van Der Meeren, O; et al.
Abstract : Aims: Combining the licensed Haemophilus influenzae type b (Hib) and serogroup C meningococcal (MenC) conjugate vaccine (Hib-MenC-TT) and DTaP-IPV vaccine could reduce the number of injections needed to administer the United Kingdom routine infant immunisation schedule. We aimed to demonstrate immunologic non-inferiority for Hib and MenC using a 6-in-1 combination vaccine (DTPa-IPV/Hib-MenC-TT) compared to a schedule using DTPa-IPV-Hib-TT and MenC-CRM197 conjugate vaccines. Secondary objectives included demonstration of non-inferiority of diphtheria, tetanus and polio immunogenicity; persistence of immune response to all antigens at 12 months of age and the response to a 12 month Hib-MenC-TT booster. Methods: Open-label, randomised, multi-centre, UK study. Combination group received DTPa-IPV/Hib-MenC-TT at 2, 3, 4 months. Control group received DTPa-IPV-Hib-TT at 2, 3, 4 months and MenC-CRM197 at 3, 4 months. Both groups received Hib-MenC-TT booster at 12 months. Concomitant vaccines: pneumococcal conjugate vaccine at 2, 4, 13 months; MMR at 13 months. Blood tests were performed at 4, 5, 12 and 13 months. Results: 142 children were randomised in each group. 100 children were included in the according-to-protocol cohort for analysis of immunogenicity following the booster vaccine in the combination group; and 112 children in the control group. One month post-primary immunisations 100% of the combination group and 93.3 % of control children had anti-PRP IgG concentration ≥0.15 μg/mL. 96.2% and 100% respectively had rSBA-MenC titres ≥1:8. One month post-booster all children met these thresholds. At 13 months of age, anti-PRP geometric mean concentrations (with 95% confidence intervals) were 66.7 (53.3-83.5) in the combination group and 26.9 (20.9-34.6) in the control group (4.35 [3.51-5.39] and 3.04 [2.21-4.19] respectively at 5 months). rSBA-MenC geometric mean titres (GMTs) were 3062.9 (2421.2-3874.6) and 954.0 (761.3-1195.5) respectively (393.2 [292.5-528.7] and 3110.5 [2612-3704.2] respectively at 5 months). Conclusion: Non-inferiority of DTPa-IPV/Hib-MenC-TT compared to DTPa-IPV-Hib-TT plus MenC-CRM197 was demonstrated. The lower rSBA-MenC GMTs after primary immunisations and greater booster responses in the combination group suggest that immune priming might be inversely related to post-primary antibody responses. Furthermore, greater immunogenicity of TT conjugates used in primary and booster MenC vaccines in this group may be important.